P0071 Faecal calprotectin as an early biomarker of colorectal anastomotic leak. (July 2015) - Morandi, E.; Monteleone, M.; Merlini, D.A.; Vignati, G.; D'Aponte, T.; Castoldi, M.
Abstract : Background: Although the early diagnosis of an anastomotic leak is a key point in reducing its clinical consequences, in daily practice this diagnosis appears later than it should. Faecal calprotectin is a protein that binds calcium and zinc, and belongs to the S100 family expressed mainly by neutrophils, and has important extracellular activity. Faecal calprotectin is used to assess active inflammation in patients with inflammatory bowel disease and colorectal cancer. Colorectal cancer is associated with a local acute inflammatory reaction of variable intensity. Several studies have assessed the role of C-reactive protein (CRP) as an early marker of anastomotic leakage, but studies into the role of faecal calprotectin to predict anastomotic failure have never been described in scientific literature. We aimed to determine whether faecal calprotectin is a predictor of anastomotic leak in colorectal surgery. Methods: The study was performed on 100 consecutive patients with diagnosed colorectal cancer admitted to hospital for an operation. Data were collected on: demographical, surgical, ASA class, and morbidity. During the first four postoperative days, faecal calprotectin, C-reactive protein, leucocytes, haemoglobin, platelets, and vital signs were evaluated. Findings: Nine (9%) patients developed a major anastomotic leak (needing reoperation) and two patients needed abdominal drainage. 4 days after surgery faecal calprotectin was significantly higher (>300 μg/g; normal value <90 μg/g) in patients who developed anastomotic leakage than those who did not develop any complications. The association between faecal calprotectin value and a CRP cutoff value of 12 mg/dL yielded a sensitivity of 85%, a specificity of 95%, and a negative predictive value of 95% for the detection of anastomotic leakage. Interpretation: Faecal calprotectin is a predictor of major anastomotic leak after colorectal resection. If raised faecal calprotectin is reported on the fourth day after surgery a careful evaluation of the patient is necessary before discharge. The increasing association between faecal calprotectin and CRP may provide a more effective way to detect an anastomotic leak.